Personification of masculine and feminine in mythological discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The peculiarities of the men’s and women’s nature in the mythological systems of ancient civilizations are given in the article on the basis of literary works. The systems are analyzed as the implementation of the mythological worldview duality.
Keywords: gender analysis; mythological systems; mythological worldview